Access to dental services for children with intellectual and developmental disabilities – A scoping review. (March 2018) - Ummer-Christian, Rahila; Iacono, Teresa; Grills, Nathan; Pradhan, Archana; Hughes, Nicole; Gussy, Mark
Highlights: The scoping review provided a map of published empirical research on access to dental services for children with IDD in the last 17 years. Key issues were identified according to the conceptual access framework. The issues were themed under dimensions of Accessibility, Availability, Affordability, Accommodation, Acceptability, and Appropriate. There is a need to conduct research into the extent of understanding of disability legislation and policies among dental service providers. Abstract: Background: Children with Intellectual and Developmental Disabilities (IDD) face considerable challenges in participating in dental services. These challenges include resource constraints and inadequate skills of health service providers to work with this population. Aim: The aim was to scope published studies that addressed access to dental services for children with IDD in order to determine the extent to which various barriers have been researched, using an access framework derived from the literature. Access was defined to include the six dimensions of accessibility, availability, affordability, accommodation, acceptability, and appropriateness. Method: Arksey and O'Malley's scoping review framework was used. Relevant databases (e.g., Medline) were searched for all empirical studies conducted from January 2000 to February 2017 that met inclusion criteria. Data were extracted along the six dimensions of the access framework. Results: Sixteen international studies were identified which indicated common key barriers to dental service use: the difficulties of physical inaccessibility, lack of access to information among carers, lack of knowledge of disability issues, and low experience and skills in caring for children with IDD among dental practitioners. Conclusions: Key recommendations made were exploring dental practitioners' understanding of disability legislation and developing training for practitioners to expand on issues specific to IDD.